2020
DOI: 10.1128/jvi.01727-19
|View full text |Cite
|
Sign up to set email alerts
|

Weak cis and trans Interactions of the Hemagglutinin with Receptors Trigger Fusion Proteins of Neuropathogenic Measles Virus Isolates

Abstract: Measles virus (MeV) is an enveloped RNA virus bearing two envelope glycoproteins, the hemagglutinin (H) and fusion (F) proteins. Upon receptor binding, the H protein triggers conformational changes of the F protein, causing membrane fusion and subsequent virus entry. MeV may persist in the brain, infecting neurons and causing fatal subacute sclerosing panencephalitis (SSPE). Since neurons do not express either of the MeV receptors, signaling lymphocytic activation molecule (SLAM; also called CD150) and nectin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Alternatively, there is no proof that such a virus would be able to attach to any cell in absence of H and thus go through the first event allowing the entry in the CNS. Additionally, other hyperfusogenic mutants more stable and also observed in encephalitis cases were shown to conserve there dependence on H for F triggering [40], reinforcing the idea that at least a low affinity neural receptor should allow the initial entry in a CNS cell [186].…”
Section: Mev Tropismmentioning
confidence: 85%
“…Alternatively, there is no proof that such a virus would be able to attach to any cell in absence of H and thus go through the first event allowing the entry in the CNS. Additionally, other hyperfusogenic mutants more stable and also observed in encephalitis cases were shown to conserve there dependence on H for F triggering [40], reinforcing the idea that at least a low affinity neural receptor should allow the initial entry in a CNS cell [186].…”
Section: Mev Tropismmentioning
confidence: 85%
“…Specifically, the T461I substitution in the F protein conferred enhanced fusion activity and contributed to MeV spread in neurons. This hyperfusogenic virus spread in cells lacking SLAM and nectin-4 [ 62 ] and infected the CNS, causing lethal disease [ 63 ]. The above studies open up new avenues for researching as yet unidentified CDV receptors and the underlying neuropathogenesis mechanism(s).…”
Section: Receptors That Enable CDV Entry and Spreadmentioning
confidence: 99%
“…Despite viral spread, there is little evidence of MeV-induced cell death, syncytium formation, or infectious virus production in neurons, while MeV RNA continues to persist in the CNS [ 61 , 69 ]. Since neurons, which are important cell targets affected in SSPE, express neither SLAM nor nectin-4, CDV is thought to exploit a different infection mechanism that does not involve these two receptors [ 62 ]. Early research on the spread of MeV between neurons indicated that MeV adopts a trans-synaptic mode of spread and does not require CD46 expression [ 61 , 70 ].…”
Section: CDV Invasion and Pathogenicity In The Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The H protein binds to receptors on the human cells and subsequently triggers the conformational changes of the trimeric F protein from the prefusion form to the postfusion form, leading to virus-to-cell or cell-to-cell membrane fusion. While the wild-type (WT) F protein cannot induce membrane fusion in neurons lacking MeV receptors [signaling lymphocytic activation molecule family member 1 (SLAMF1) and nectin-4], hyperfusogenic mutant F proteins from SSPE patientderived MeV strains can do so by using cell adhesion molecule 1 (CADM1) and CADM2 as "cis-acting receptors" (host factors triggering fusion in cis) (12)(13)(14). The H protein interacts with CADM1 and CADM2 in cis on the same membrane, triggering the conformational changes of the hyperfusogenic mutant F proteins but not of the WT F protein.…”
Section: Introductionmentioning
confidence: 99%